Bwindi-Sarambwe 2018 Surveys Monitoring Mountain Gorillas, Other Select Mammals, and Human Activities - Hickey, Jena R.; Uzabaho, Eustrate; Akantorana, Moses; Arinaitwe, Joseph; Bakebwa, Ismael; Bitariho, Robert; Eckardt, Winnie; Gilardi, Kirsten; Katutu, Jacques; Kayijamahe, Charles (Bwindi Impenetrable National park, 2019)
Long-term monitoring of wildlife populations allows population trends to be characterized from periodic robust abundance estimates. Based on those derived trends, conservation status of the species and conservation efforts may both be assessed. As such, for decades researchers and Protected Area Authorities have estimated the abundance of mountain gorillas in both Bwindi Impenetrable National Park and the Virunga Massif through collaborative survey efforts. Here, we report on the results of the Bwindi 2018 surveys of mountain gorillas, other select mammals ,and human activities. As in recent surveys(e.g. Roy et al 2014, Hickeyet al 2019, Granjon et al in press), field teams walked pre-determined compass bearings termed ‘reconnaissance trails’ through the forest of the Bwindi-Sarambwe ecosystem in two separate sweeps to ensure thorough coverage of all areas while searching for signs of mountain gorillas, other select mammals, and illegal activities. When a fresh or recent gorilla trail was detected, the teams followed it to locate, optimally, three recent nest sites for each gorilla group or solitary individual. At each of these sites, the teams collected fecal samples from gorilla nests(Photo 1) that were genotyped to individual for a minimum count of mountain gorillas in the Bwindi-Sarambwe ecosystem. We estimated a minimum count of 459 gorillas based on the number of unique consensus genotypes of un monitored gorillas (n=263) detected during this survey plus the known number of monitored gorillas (n=196). A minimum count does not equate to a total population estimate because not all gorillas are detected in such surveys. For example, only 1 of 13 solitary individuals and 14 of 33 un monitored groups were detected in both sweep 1 and 2. The remaining gorillas were only detected in one of the two sweeps. Therefore, detection probabilities and an associated total abundance estimate for the Bwindi-Sarambwe sub population of mountain gorillas are forth coming in a separate document pending further mark-recapture analyses following similar previous approaches (Roy et al 2014, Granjon et al in press).Compared to the 2011 survey estimate of 400 individual gorillas (an estimate that included correction factors for 37 infants and/or individuals that were potentially undetected in the genetic analysis; Robbins et al 2013, Roy et al 2014), the 2018 minimum count of 459 gorillas (that included no correction factors and is a true minimum) confirms that the Bwindi-Sarambwe mountain gorilla population grew during the intervening period. Photo 1. Team members prepare for biological sampling ©Jena R Hickey 6 Although two sweeps were conducted in 2011 for estimating the gorilla abundance, only one sweep in 2011 included the survey of other large mammals and human activities. Therefore,the 2018 Bwindi-Sarambwe Survey represents approximately twice the effort made in 2011 in terms of total kilometers walked while recording other select mammals and human activities(IGCP un pub. data). The field sampling effort for the second sweep in 2011and each individual sweep in 2018 was sufficiently comparable in terms of distance walked that we assumed that detection probabilities of mammal and human-activity signs were similar in each individual sweep, and that all three sweeps could thus be compared to each other. For comparing within the same season, the second sweep of both 2011 and 2018 took place from September to December. Sightings of black-fronted duikers (Cephalophus nigrifons), bushbucks(Tragelaphus scriptus), and bush pigs (Potamochoerus larvatus) all had roughly similar encounter rates in 2011 and 2018, whereas all other mammals surveyed exhibited much higher encounter rates in 2018 than in 2011. For example, we recorded 0.615 and 0.725 encounters/km for elephant dung, in sweeps 1 and 2 of 2018 respectively, whereas 0.518 encounters/km were reported in 2011. For chimpanzee nests, we recorded 0.463 and 0.679 encounters/km in sweeps 1 and 2 of 2018,respectively, whereas 0.288 encounters/km were recorded in 2011.While we do not infer population trends from surveys of indirect signs, these data suggest at least a relatively stable status for the other select mammals surveyed, as they provide no indications of population declines since 2011. The information collected will inform species-distribution models for a better understanding of the population ecology of several species of mammals in relation to abiotic and biotic factors, including the potential influence of human activities in shaping their spatial distributions. Data suggest that illegal activities in the Bwindi-Sarambwe ecosystem also have not declined since 2011, despite formidable conservation efforts in both law enforcement and community engagement. For example, the survey teams destroyed 88 snares during the 2018 surveys. Snare encounter rates were roughly similar between 2011 and 2018; we recorded 0.042 and 0.055 encounters/km in sweep 1 and 2 of 2018, respectively, compared to 0.058 encounters/km reported in 2011. For comparison, snare-encounter rates in the Virunga Massif were reported as 0.15 and 0.09 snare encounters/km in 2015 and 2016,respectively(Hickey et al 2019), suggesting that although snareen counter rates observed in Bwindi-Sarambwe appear not to have declined since
Field Survey
Keywords: Bwindi-Sarambwe 2018 Surveys; Monitoring Mountain Gorillas; Select Mammals